Resistance of gastrointestinal nematodes to anthelmintics in sheep (Ovis aries) - Thomaz-Soccol,Vanete (2004)
The fecal egg count reduction test (FECRT) was used in a survey for anthelmintic resistance in 42 sheep farms, in five different regions in Paraná State, Brazil between July 1996 - July 2000. Animals with natural infection were tested. Five drugs were used individually or in combination - benzimidazole, imidazothiazole, ivermectin, milbemicina and closantel. Results showed that the prevalence of resistance to all anthelmintic was as high as 88.1% for benzimidazoles (oxfendazole), 78.6% for ivermectin, 56.4% for closantel, 38.7% for closantel + oxfendazole, 38% for levamisole, and 23.6% for moxidectin. There was multiple resistance in all tested farms. The most important infective larvae recovered from culture were Haemonchus contortus and Trichostrongylus colubriformis. The failure of the existing drugs in the State of Paraná is considered an important issue. Some proposals to improve the situation are suggested which include a change of attitude on anthelmintic use by sheepherders, veterinarians and sanitary authorities.